E-157 Multivariable outcome prediction after endovascular treatment for acute ischemic stroke: development of a prognostic model in data from seven randomized controlled trials. (22nd July 2018) - Chalos, V; Venema, E; Mulder, M; Roozenbeek, B; Brown, S; Demchuk, A; Majoie, C; Muir, K; Dávalos, A; Mitchell, P; Bracard, S; Hill, M; et al.
Abstract : Purpose: Even when the revascularization and clinical status of a patient after endovascular treatment (EVT) for acute ischemic stroke is known, outcome is still highly variable and difficult to predict. We aimed to develop a prognostic model that can be applied within one day after EVT to predict functional outcome at three months. Methods: We used data from patients in the treatment arms of seven randomized controlled trials within the HERMES collaboration (MR CLEAN, ESCAPE, REVASCAT, SWIFT-PRIME, EXTEND-IA, THRACE, and PISTE). Primary outcome was the ordinal modified Rankin Scale (mRS) score three months after EVT. Fifteen pre- and post-procedural variables, assessed within one day after EVT, were analyzed with univariable ordinal logistic regression analysis and multivariable ordinal logistic regression analysis with stepwise backward selection (p<0.157), and a fixed effect for trial. From this model, we derived predicted probabilities of functional independence (mRS 0–2) and survival (mRS 0–5). Model performance was quantified with the c-statistic. Internal validation with bootstrapping was performed to estimate the degree of optimism in the final model. To correct for this optimism we reduced the regression coefficients by using penalized regression. Results: The final model, based on 781 patients, included nine variables and explained 62.4% of the variance in outcome. Pre-procedural variables included age, diabetes mellitus, pre-stroke mRS, collateral vessel grade, occlusion location, and time from stroke onset to groin puncture. Post-procedural variables included revascularization grade, stroke severity measured with the National Institutes of Health Stroke Scale (NIHSS), and symptomatic intracranial hemorrhage. The NIHSS was the strongest predictor with 53.9% explained variance. The internally validated c-statistic was 0.83 for the prediction of the ordinal mRS, 0.89 for functional independence, and 0.80 for survival, indicating good model performance. Conclusions: This model, which can be applied within one day after EVT, accurately predicts functional outcome at three months. It may provide physicians, patients, and family members with improved outcome expectations and improve decision making by personalizing the patients' treatment and rehabilitation plan. Disclosures: V. Chalos: None. E. Venema: None. M. Mulder: None. B. Roozenbeek: None. S. Brown: 2; C; Medtronic. A. Demchuk: 1; C; Covidien (Medtronic). 6; C; Covidien (Medtronic). C. Majoie: 1; C; Stryker. K. Muir: 1; C; Medtronic, Codman, Stroke Association, National Institute of Health Research (NIHR) Health Technology Assessment programme. 2; C; Medtronic. A. Dávalos: 2; C; Medtronic Neurovascular. P. Mitchell: 1; C; Covidien (Medtronic), Medtronic, Stryker, Codman Johnson and Johnson. 2; C; Codman Johnson and Johnson. S. Bracard: None. M. Hill: 1; C; Covidien (Medtronic), Heart and Stroke Foundation, Alberta Innovates Health Solutions, Alberta Health Services. 4; C; Calgary Scientific Incorporated. 6; C; Merck, Hoff mann-La Roche Canada ltd. P. White: 1; C; Medtronic, Codman, Stroke Association, National Institute of Health Research (NIHR) Health Technology Assessment programme. 6; C; Microvention Terumo, Codman. B. Campbell: 1; C; Covidien (Medtronic), National Health and Medical Research Council of Australia, Royal Australasian College of Physicians, Royal Melbourne Hospital Foundation, National Heart Foundation, National Stroke Foundation of Australia, Royal Melbourne Hospital Foundation. F. Guillemin: None. J. Saver: 1; C; Medtronic, Stryker. 2; C; Medtronic/Covidien, Neuravi, Stryker, BrainsGate, Pfizer, Squibb, Boehringer Ingelheim (prevention only), ZZ Biotech, St. Jude Medical, Genentech. 4; C; Cognition Medical. T. Jovin: 2; C; Codman Neurovascular, Stryker, Neuravi, Medtronic. 4; C; Blockade, Silk Road. M. Goyal: 1; C; Medtronic, Stryker. 6; C; Medtronic, Stryker, Microvention, GE Healthcare. A. van der Lugt: 1; C; Dutch Heart Foundation, Dutch Brain Foundation, Stryker, Medtronic, Penumbra. 2; C; Stryker. D. Dippel: 1; C; Dutch Heart Foundation, Dutch Brain Foundation, AngioCare BV, Medtronic/Covidien/EV3, MEDAC Gmbh/LAMEPRO, Penumbra Inc, Stryker, Top Medical/Concentric. 2; C; Stryker, Bracco Imaging. H. Lingsma: None.